DISTRIBUTION PATTERNS OF DIFFERENT FORMS OF PHOSPHORUS IN SOME SURFICIAL SEDIMENTS OF THE BALTIC SEA - Carman R.; Jonsson P. (My University, 1991)
The lateral distribution patterns of different forms of phosphorus (P) in some Baltic Sea sediments were investigated by a sequential extraction procedure. The distribution and amount are mainly related to redox state, grain size, organic content and the chemical characteristics of the sediments. Recalculation from mol P per dry weight (d.w.) to mol P per unit area indicates that coarse sediments typical of transportation bottoms contain more total P than the finer sediments found in accumulation areas. This is applicable for almost all extracted P fractions. The extraction procedure shows that HCl-extractable P, often referred to as apatite-P, is the dominating fraction of almost all sediment types. Oxidized fine-grained sediments of the near-shore area and the archipelago are enriched in the hydrogen sulfide (H2S) extractable P fraction.